Study on the impact of plastic pollution based on multiple regression model. Issue 1 (May 2021) - Zhu, Guanlin; Tang, Chenyang; Zhang, Benyin
Abstract: Plastic has become an indispensable and important part of human beings. In the past decades years, using plastic we have found that their biggest advantage is the disadvantage of causing fatal effects on the environment. The worsening of plastic pollution also makes us learn the severity of the problem gradually. We have established an evaluation model and adopted a local analysis method to global analysis method to analyze the impact of plastic pollution.